TRANSPARANSI DAN AKUNTABILITAS TATA KELOLA PEMERINTAHAN DAERAH DALAM HUBUNGANNYA DENGAN PERWUJUDAN KEADILAN DAN KINERJA PEMERINTAH DAERAH: SUDUT PANDANG APARATUR DAN MASYARAKAT DI ERA OTONOMI DAERAH - Pratolo, Suryo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2008)
This research examine the relationship among transparency, accountability, fairness, and performance of Wonosobo Local Government. There are two point of views (public and government officer perceptions) used in this research. Based on secondary data, path analysis was used to test the five hipotheses. The result of the analysis are: both transparancy dan accountability influence government performance. Transparency influence government’s performance directly while accountability influence on government performance indirectly through fairness. Each variable is on unoptimum level, so it can be concluded that the unoptimum government performance and fairness is influenced by unoptimum transparency and accountability. Based on this conclusions, it can be suggested to the local government in improving the transparancy and accountability to gain maximum government’s fairness and performance.